Model of Disintegration Prevention in the Tidore Community Based on Social Capital (Dama Nyili-Nyili Tradition) - Putri Nurdiana Jailan; Burhanudin A Muhammad (Yayasan Ilomata, 2026)
Tidore is an archipelagic region that faces challenges in achieving equitable development and is characterized by a multi-clan social structure. At certain times, inter-clan fanaticism can lead to domination and social conflict. Therefore, research on a Social Capital-Based Model for Preventing Disintegration in the Tidore Community through the Dama Nyili-nyili Tradition is essential, as the values embedded in each stage of this tradition are considered sacred and play a significant role in maintaining social harmony and mitigating the risk of disintegration. This study aims to provide a stimulus for the Tidore community and relevant stakeholders to preserve and utilize the dama nyili-nyili tradition as a reference framework for fostering unity and cohesion within a heterogeneous society. A qualitative research approach was employed, with the research conducted on the islands of Tidore, Mare, and Maitara. Data were collected through in-depth interviews with traditional leaders, religious leaders, and community leaders as primary sources. The study specifically focuses on a disintegration prevention model derived from the traditional values of dama nyili-nyili, distinguishing it from previous studies in terms of analytical substance. The findings indicate that the Dama Nyili-nyili tradition continues to exist and is actively preserved by the Tidore community. The proposed model for preventing social disintegration consists of three key elements: tolerance education as a fundamental social value within the Tidore community, strengthening customary institutions as symbols of traditional governance, and reinforcing mutual cooperation as a foundation of social cohesion.